Decentralization and Public Participation: A Literature Review on Impact and Implementation - Dana Mulanda; Aldri Frinaldi; Lince Magriasti (STIA Adabiah, 2024)
This study examines the correlation between decentralization and community engagement in local government administration in Indonesia. This study examines the impact of decentralization measures enacted during the reform era on the extent of community involvement in local decision-making processes. The data originates from surveys and interviews conducted with diverse stakeholders in many locations in Indonesia. The research findings indicate that decentralization has facilitated community engagement in local government administration. However, various barriers hinder broader and more efficient participation.